Sexual abuse of minors by clergy in cinematography: unrecognized signs of the times - Marek Lis (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2022)
Contemporary theologians apply the historic notion of loci theologici also to media and film. Films that show the Church in a critical way are also theologically significant. Therefore, one should be aware of the appearance of documentaries and feature films, which raise the issue of sexual abuse against the youngest (paedophilia) also in the Church. The article presents the most important films, produced since the end of the 20th century, whose authors present the crime of paedophilia, its victims, the mechanisms leading to its concealment and silence not only in the Church, but also in the media and society. Films about paedophilia, which are a recognisable voice of victims in the public space, a cry for truth and justice, can also be useful tools for media education.